A review of social inclusion measures. (October 2013) - Coombs, Tim; Nicholas, Angela; Pirkis, Jane
Background: Social inclusion is crucial to mental health and well-being and is emphasised in Australia's Fourth National Mental Health Plan . There is a recognition that a measure of social inclusion would complement the suite of outcome measures that is currently used in public sector mental health services. This paper is an initial scope of candidate measures of social inclusion and considers their suitability for this purpose. Methods: We identified potential measures through searches of PsycINFO and Medline and a more general Internet search. We extracted descriptive and evaluative information on each measure identified and compared this information with a set of eight criteria. The criteria related to the measure's inclusion of four domains of social inclusion outlined in Australia's Fourth National Mental Health Plan, its usability within the public mental health sector and its psychometric properties. Results: We identified 10 candidate measures of social inclusion: the Activity and Participation Questionnaire (APQ-6); the Australian Community Participation Questionnaire (ACPQ); the Composite Measure of Social Inclusion (CMSI); the EMILIA Project Questionnaire (EPQ); the Evaluating Social Inclusion Questionnaire (ESIQ); the Inclusion Web (IW); the Social and Community Opportunities Profile (SCOPE); the Social Inclusion Measure (SIM); the Social Inclusion Questionnaire (SIQ); and the Staff Survey of Social Inclusion (SSSI). After comparison with the eight review criteria, we determined that the APQ-6 and the SCOPE–short form show the most potential for further testing. Conclusions: Social inclusion is too important not to measure. This discussion of individual-level measures of social inclusion provides a springboard for selecting an appropriate measure for use in public sector mental health services. It suggests that there are two primary candidates, but neither of these is quite fit-for-purpose in their current form. Further exploration will reveal whether one of these is suitable, whether another measure might be adapted for the current purpose or whether a new, specifically designed measure needs to be developed.